From Planning to Design: Implications of the Life Design Paradigm for the Reform of Career Education Curriculum - Ling, Hairong; Song, Chunze (Journal of Research in Vocational Education, 2025)
There are currently three main career education paradigms, namely the matching-oriented career guidance paradigm, the development-oriented career guidance paradigm, and the construction-oriented life design paradigm. Different career education paradigms have different understandings of career, educational subjects, educational purposes, and educational strategies. Compared with the first two paradigms, the life design paradigm, which originated in the postmodern society, aims to cultivate students’ ability to actively construct and manage their own careers to cope with the uncertain VUCA era and has a greater enlightening effect on the development of career education courses. In terms of educational concepts, there is a shift from static “person-job fit” to dynamic “career construction”, focusing on the subjective initiative of students in career development and the continuous constructiveness of situations on students’ career development. In terms of curriculum objectives, it focuses on students’ initiative, narrative and adaptive development. In terms of curriculum content, starting from the theme of students’ career development, it integrates related content such as self-awareness, environmental exploration, decision-making planning, psychology, interpersonal relationships, etc., emphasizing the design of content that is coherent as whole. In terms of course implementation, the problem-solving career education steps provide a reference for classroom teaching and pay more attention to the use of indirect and direct experience mixed methods such as metaphor, life story, role model, career practice, etc. In terms of course evaluation, attention should be paid to the construction of the fractal model of the intervention effect, and indicators such as students’ career adaptability, hope, and career exploration should be given particular attention.